2004
DOI: 10.1507/endocrj.51.31
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Molecular Analysis and HLA Typing of Late-onset 21-Hydroxylase Deficiency in Turkish Woman with Hirsutism and Polycystic Ovary

Abstract: Abstract. We studied the incidence of late-onset congenital adrenal hyperplasia (LOCAH) due to 2l-hydroxylase (21-OH) deficiency, its molecular genotype expression, and its association with the major histocompatibility complex in 61 women with hirsutism and polycystic ovary. Ultrasound, clinical and hormonal parameters were used to define polycystic ovary syndrome (PCOS). Baseline and ACTH stimulated 17a-hydroxyprogesterone (17-OHP) levels were measured for screening of LOCAH during follicular phase. Forty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
3
15
0
2
Order By: Relevance
“…These findings are in agreement with our previous paper on the high frequency and the positively genetic linkage disequilibrium of HLA phenotypes B14, DR 1 , B 35 , B 47 , B 22 and B 7 and 21-OHdef in Greece [41]. In group C (that, is the group of women with PCOS) there are a considerably great number of women with 17-OHP 60 values between 21 nmol/l and 32 nmol/l (10 out of 22) (45%).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in agreement with our previous paper on the high frequency and the positively genetic linkage disequilibrium of HLA phenotypes B14, DR 1 , B 35 , B 47 , B 22 and B 7 and 21-OHdef in Greece [41]. In group C (that, is the group of women with PCOS) there are a considerably great number of women with 17-OHP 60 values between 21 nmol/l and 32 nmol/l (10 out of 22) (45%).…”
Section: Discussionsupporting
confidence: 94%
“…As previously reported, the prevalence of 21-OHdef varies from 1% to 20%-30% and it is particularly high around the Mediterranean, in Italians, in the Jewish Ashkenazi, in the Hispanics, in the Turks and in the Arabs [34][35][36][37][38]. Recently published papers in Turkey, reported a high prevalence of NC-CAH due to 21-OHdef in women suffering from hirsutism and PCOS [11,34,35].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although there were some studies regarding the prevalence of NCAH due to 21-OH deficiency among hirsute Turkish women, these studies were local, not having any detailed genotype investigation and have been performed with relatively small number of patients [17,18] study investigating the prevalence of NCAH due to 21-OH deficiency among Greek women with hirsutism and PCOS showed a relatively higher (10.3%) prevalance compared with other European communities [21]. However, diagnosis of 21-OH deficiency has not been confirmed by molecular genetic analysis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found 21-hydroxylase deficiency to be present in 33% of patients with symptoms of PCOS and hirsutism (14). The largest study (n=205) from Turkey reported a frequency of LCAH of 9.75% among patients with hirsutism (15).…”
Section: Discussionmentioning
confidence: 98%